2006
DOI: 10.1016/j.bcp.2005.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity and molecular modeling analyses of ribose- and base-modified uridine 5′-triphosphate analogues at the human P2Y2 and P2Y4 receptors

Abstract: With the long-term goal of developing receptor subtype-selective high affinity agonists for the uracil nucleotide-activated P2Y receptors we have carried out a series of structure activity and molecular modeling studies of the human P2Y2 and P2Y4 receptors. UTP analogues with substitutions in the 2'-position of the ribose moiety retained capacity to activate both P2Y2 and P2Y4 receptors. Certain of these analogues were equieffective for activation of both receptors whereas 2'-amino-2'-deoxy-UTP exhibited highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(117 citation statements)
references
References 36 publications
(76 reference statements)
5
111
1
Order By: Relevance
“…Based on current pharmacological profiling, this rank order is not consistent with that reported for P2Y 1 (ADP Ͼ UTP), P2Y 6 (UDP Ͼ UTP), P2Y 11 (ATP Ͼ Ͼ UTP), P2Y 12 (ADP Ͼ UTP), P2Y 13 (2-MeSADP ϭ ADP Ͼ UTP, ATP) or P2Y 14 (UDP-glucose Ͼ Ͼ UTP, ATP, ADP) (1,14,41). Only the rat P2Y 2 and P2Y 4 receptors have been reported to be activated preferentially and equipotently by UTP and ATP (14,26). Closer analysis revealed that UTP-and UTP␥S-evoked increases in cytosolic calcium in rat urothelial cells were mediated by the release of calcium from intracellular stores and via PLC-linked mechanisms, consistent with the mode of action of putative P2Y 2/4 receptors (3,12).…”
Section: Discussionmentioning
confidence: 88%
“…Based on current pharmacological profiling, this rank order is not consistent with that reported for P2Y 1 (ADP Ͼ UTP), P2Y 6 (UDP Ͼ UTP), P2Y 11 (ATP Ͼ Ͼ UTP), P2Y 12 (ADP Ͼ UTP), P2Y 13 (2-MeSADP ϭ ADP Ͼ UTP, ATP) or P2Y 14 (UDP-glucose Ͼ Ͼ UTP, ATP, ADP) (1,14,41). Only the rat P2Y 2 and P2Y 4 receptors have been reported to be activated preferentially and equipotently by UTP and ATP (14,26). Closer analysis revealed that UTP-and UTP␥S-evoked increases in cytosolic calcium in rat urothelial cells were mediated by the release of calcium from intracellular stores and via PLC-linked mechanisms, consistent with the mode of action of putative P2Y 2/4 receptors (3,12).…”
Section: Discussionmentioning
confidence: 88%
“…This difference in the size of the pocket seemed to be critical for the selective recognition of 5-substituted UTP derivatives. For example, 5-methyl UTP is 9.8-fold less potent than UTP at the P2Y 2 receptor, but 53-fold less potent than UTP at the P2Y 4 receptor [16].…”
Section: Comparison Of Functional Amino Acid Residues Within the Two mentioning
confidence: 99%
“…2C). For example, molecular modeling combined with SAR analysis was recently applied to study the binding modes of UTP and its analogues in the P2Y 2 and P2Y 4 receptors [16]. A conformational analysis of UTP in the binding pockets of the P2Y 2 and P2Y 4 receptors was performed by means of the mixed MCMM/LMCS sampling method as implemented in MacroModel 9.0 [22] The search was performed on the ligand and the residues located within 5 Å of the ligand, while the remaining residues were conformationally frozen.…”
Section: Comparison Of Functional Amino Acid Residues Within the Two mentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified and developed novel, selective ligands for several P2Y recep-tors that have proven useful for pharmacological resolution of molecularly defined P2Y-R in cells and tissues (Boyer et al, 1996;Houston et al, 2006Houston et al, , 2008Jacobson et al, 2006). Accordingly, we are interested in identifying a selective antagonist for the P2Y 14 -R. Ault and Broach (2006) recently used a yeast model system in which various nucleotides and nucleotide sugars were examined for their ability to stimulate growth of mutant P2Y 14 -R-expressing yeast cells in studies focused on the identification of mutant P2Y 14 receptors with differential agonist sensitivities.…”
mentioning
confidence: 99%